EVALUASI KEAMANAN SISTEM INFORMASI MANAJEMEN PERUSAHAAN ASURANSI - Nonita Fitriana Harahap; Muhammad Irwan Padli Nasution (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Management information systems are transaction management can provide important information quickly, making it easier for management to retrieve it decisions in the interests of the company. An important aspect that is often forgotten in using the system information is a matter of information security. Information security is the protection of information which aims to protect from all sources of threats. The main principles of information security are confidentiality, data integrity and availability. Efforts to maintain In order to keep information safe, an evaluation of information security risks is needed which aims to identify threats and create mitigation plans to reduce risks. The agency's protection strategy is not working well because employees are not yet there receive training on information security. To improve security, companies must pay special attention attention to work on security policy, security organization, personnel security, physical and environmental security, communications and operations management, access control and compliance.